In-situ synchrotron X-ray diffraction analysis of the elastic behaviour of martensite and H-phase in a NiTiHf shape memory alloy fabricated by laser powder bed fusion - Shen, Jiajia (2022)
UID/00667/2020 CSC NO. 201808320394 2020ZDZX0015 I-20200633